How shopping satisfaction contributes to internationaltourism satisfaction and tourism expenditures by gender: Analysis of U.S. tourists in South Korea - Middaugh, J.; Kwak, L.E.; Meng, F. (International Journal of Business Research, 2013)
The purpose of the study was to examine how international tourists' shopping satisfaction related to their overall satisfaction as tourists and the tourists' expenditure differences by gender. A survey was conducted among U.S. citizens of who were traveling to South Korea (n = 422). The survey took place at transport hubs of the major international airports and seaports in South Korea prior to tourists' departure. The findings of this research concluded that tourist shopping satisfaction was significantly correlated with overall tourist satisfaction. In addition, different shopping patterns were reported among men and women tourists. The results of this study confirm that a positive retail shopping experience is an important aspect of overall international tourism.
Keywords: Gender; Shopping satisfaction; United States tourists; dept.mkt; peer-reviewed

Use of comforting to enhance social marketing success A case study - Forbus, Robert; Snyder, Jason L (Social Marketing Quarterly, 2013)
Successful behavioral change is the Holy Grail for social marketers. Meta-analysis demonstrates that effect sizes of behavioral change in social marketing campaigns is typically low. The present case study uses 4 years of survey data from an Alabama weight loss and behavioral change campaign to develop an explanation for why some people are more successful in lifestyle change efforts than others. Comforting, a communicative form of prosocial behavior, produced the greatest magnitude of change when tested as an independent variable on dependent variables, including pounds lost, amount of dairy products and water consumed, and physical activities undertaken. The case study concludes by discussing implications for social marketing academics and practitioners. © The Author(s) 2013.
Keywords: Behavioral change; Comforting; Social marketing campaigns; Social support; Weight loss; dept.mkt